Interreligiöse Kooperation im Religionsunterricht: Perspektiven und Zwischenfazit zum Lernen in heterogenen Lerngruppen - Kamcili-Yildiz, Naciye; Woppowa, Jan; Caruso, Carina; Konsek, Lukas (Religion in der Schule. Pädagogische Praxis zwischen Diskriminierung und Anerkennung)

,Dann mache ich einfach mal weiter.‘ – Zur Lehrsteuerung der Studierenden in die Indifferenz - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Mindsets religiöser Pluralität als Faktor in der (islamischen) Religionslehrer*innenbildung - Kamcili-Yildiz, Naciye; Mauritz, Gerrit; Reis, Oliver; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik)

Pluralisation of Theologies at European Universities

Säkular und religiös: Herausforderungen für Christentum und Islam

Lesen lernen von Aufgabentexten - Dröse, Jennifer; Prediger, Susanne (Sprachbildender Mathematikunterricht in der Sekundarstufe - ein forschungsbasiertes Praxisbuch)

Physik in der Lehrerinnen- und Lehrerbildung. Auf dem Weg zu empirisch fundierten Curricula - Reinhold, Peter; Riese, Josef (Handbuch Lehrerinnen- und Lehrerbildung)

Die Messung der Fähigkeit zur Unterrichtsplanung im Fach Physik mit Hilfe eines standardisierten Performanztests - Schröder, Jan; Riese, Josef; Vogelsang, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Die Unterrichtsplanung stellt eine zentrale berufliche Anforderung an (Physik‑)Lehrkräfte dar. Bereits im Lehramtsstudium sollen grundlegende Fähigkeiten zur Unterrichtsplanung erworben und im Rahmen von schulpraktischen Phasen erprobt bzw. erweitert werden. Unklar ist jedoch, inwieweit das professionelle Wissen, das Lehramtsstudierende in ihren fachlichen, fachdidaktischen und erziehungswissenschaftlichen Studienteilen erwerben, tatsächlich bei der Planung von Fachunterricht genutzt wird. Ebenso gibt es nur punktuelle Erkenntnisse über die Entwicklung der Fähigkeit zur Unterrichtsplanung im Lehramtsstudium. Um diese Fragen zu klären, sind Messverfahren erforderlich, die die Fähigkeiten zur Unterrichtsplanung valide erfassen können und die gleichzeitig ökonomisch auswertbar sind, um Fallzahlen realisieren zu können, die auch kleine Effekte auflösen. Bisherige Ansätze, die reale Handlungsproben der Unterrichtsplanung (z. B. schriftliche Unterrichtsentwürfe) untersuchen, stehen vor der methodischen Herausforderung, dass die Generierung eines Fähigkeitsmaßes höchst anspruchsvoll ist, da reale Planungen individuell sehr unterschiedlich angelegt sind und vielen Randbedingungen unterliegen, die statistisch kaum kontrollierbar sind. In diesem Beitrag wird daher ein sogenannter Performanztest zur Erfassung der Fähigkeit zur Unterrichtsplanung vorgestellt und diskutiert. Ein Performanztest ist ein Verfahren, in dem in einem realitätsnahen Setting Handlungen unter standardisierten Rahmenbedingungen simuliert werden. Neben der theoriegeleiteten Entwicklung des Instruments und Vorstudien zur Sammlung von Validitätsargumenten werden auch erste Ergebnisse dargestellt, die aus Erhebungen vor und nach einem Praxissemester an vier Universitäten in drei Bundesländern resultieren ( N = 174 Unterrichtsplanungen). Dabei stellt sich das Testverfahren als ausreichend sensitiv heraus, um für N = 68 Testpersonen (ca. 20 % Dropout) erwartungstreu eine signifikante Zunahme des Testscores während des Praxissemesters, welches als Lerngelegenheit angenommen werden kann, zu messen.

Development of Prospective Physics Teachers’ Professional Knowledge and Skills during a One-Semester School Internship - Vogelsang, Christoph; Borowski, Andreas; Kulgemeyer, Christoph; Riese, Josef; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Schecker, Horst; Schröder, Jan (Student Learning in German Higher Education)

Professional knowledge affects action-related skills: The development of preservice physics teachers’ explaining skills during a field experience - Kulgemeyer, Christoph; Borowski, Andreas; Buschhüter, David; Enkrott, Patrick; Kempin, Maren; Reinhold, Peter; Riese, Josef; Schecker, Horst; Schröder, Jan; Vogelsang, Christoph (Journal of Research in Science Teaching)
Keywords: Education

Mindsets guter Lehre in Beziehung zu den Mindsets religiöser Pluralität - Kamcili-Yildiz, Naciye; Reis, Oliver; Mauritz, Gerrit; Hillebrand, Miriam; Wittke, Annika (Theo-Web. Zeitschrift für Religionspädagogik, 19)

The Story of Mary as a Feminine Counterpart to the Story of Joseph - Haghani Fazl, Mohammad (Religious Inquiries, 9)

Adhesion of HVOF-Sprayed WC-Co Coatings on 316L Substrates Processed by SLM - Tillmann, Wolfgang; Hagen, Leif; Schaak, Christoph; Liß, J.; Schaper, Mirko; Hoyer, Kay-Peter; Aydinöz, Mehmet Esat; Garthe, Kai-Uwe (Journal of Thermal Spray Technology)
Abstract Different studies have been demonstrated that the surface integrity of substrate bulk materials to be coated has a significant impact on the adhesion of thermally sprayed coatings. It is known that the surface integrity of parts processed by selective laser melting (SLM) differs from those obtained from bulk materials. Although 316L stainless steel is among the most investigated material for SLM, the adhesion of thermally sprayed coatings on 316L stainless steel substrates processed by SLM has not been studied yet. This study aims at evaluating the effect of various mechanical pre-treatments onto 316L stainless steel substrates processed by SLM and their effect on the adhesion of high velocity oxy-fuel (HVOF)-sprayed WC-Co coatings. To differentiate between topographical effects and residual stress-related phenomena, a stress-relief heat treatment of the SLM substrates served as a reference throughout the investigations. The differently pre-treated SLM substrates were investigated with regard to the surface roughness and residual stresses. For the HVOF-sprayed SLM composites, Vickers interfacial indentation tests were conducted to assess the resulting coating adhesion. The findings demonstrated that the HVOF-sprayed WC-Co coatings predominantly exhibit good adhesion to the SLM 316L substrates. However, it was found that the stress state in the SLM 316L substrate surface is more likely to affect the adhesion of the WC-Co coating, while the substrate surface roughness showed a marginal effect.
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Condensed Matter Physics

Effect of substrate pre‐treatment on the low cycle fatigue performance of tungsten carbide‐cobalt coated additive manufactured 316 L substrates - Tillmann, Wolfgang; Hagen, Leif; Garthe, Kai-Uwe; Hoyer, Kay-Peter; Schaper, Mirko (Materialwissenschaft und Werkstofftechnik)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Characterization of Phase Transformations During Graded Thermo-Mechanical Processing of Press-Hardening Sheet Steel 22MnB5 - Reitz, Alexander; Grydin, Olexandr; Schaper, Mirko (Metallurgical and Materials Transactions A)
Abstract Safety-relevant components in automobiles require materials that combine high strength with sufficient residual ductility and high-energy absorption. A graded thermo-mechanical treatment of the press-hardening steel 22MnB5 with graded microstructure can provide a material with such properties. Different austenitization temperatures, cooling and forming conditions within a sheet part lead to the development of microstructures with mixed phase compositions. To determine the resulting phase contents in such graded processed parts, a large number of dilatometric tests are usually required. With a non-contact characterization method, it is possible to detect local phase transformations on an inhomogeneously treated flat steel specimen. For press-hardening steel after heat treatment and thermo-mechanical processing, correlations between austenitization temperature, hot deformation strain, microstructure, and hardness are established.

New Twin-Roll Cast Al-Li Based Alloys for High-Strength Applications - Grydin, Olexandr; Stolbchenko, Mykhailo; Schaper, Mirko; Belejová, Sára; Králík, Rostislav; Bajtošová, Lucia; Křivská, Barbora; Hájek, Michal; Cieslar, Miroslav (Metals)
Al-Li based alloys are attractive materials for the aerospace industry. The twin-roll casting of such materials could provide properties not achievable by conventional direct-chill casting and downstream processing methods due to significantly higher solidification rates. An Al-Li-Cu-Mg-Zr alloy was twin-roll cast with the same alloy containing a small addition of Sc. The microstructure of as-cast materials and the influence of Sc on the behavior of the alloy at elevated temperatures were studied by means of light and electron microscopy and by resistivity measurements. A fine-grained structure was formed during twin-roll casting, but several surface and internal defects were found on the strips, which should be suppressed by a further adjustment of the casting conditions. The addition of Sc had a positive effect on grain size uniformity and microstructure stabilization at elevated temperatures, as shown by the precipitation of a fine dispersion of coherent Sc- and Zr-containing precipitates.

Nano-architectural complexity of zinc oxide nanowall hollow microspheres and their structural properties - Engelkemeier, Katja; Lindner, Jörg; Bürger, Julius; Vaupel, Kathrin; Hartmann, Marc; Tiemann, Michael; Hoyer, Kay-Peter; Schaper, Mirko (Nanotechnology)
Zinc oxide (ZnO) hollow spheres with defined morphology and micro-/nanostructure are prepared by a hydrothermal synthesis approach. The materials possess fine-leaved structures at their particle surface (nanowall hollow micro spheres). Morphology control is achieved by citric acid used as an additive in variable relative quantities during the synthesis. The structure formation is studied by various time-dependent ex situ methods, such as scanning electron microscopy, x-ray diffraction, and Raman spectroscopy. The fine-leaved surface structure is characterized by high-resolution transmission electron microscopy techniques (HRTEM, STEM), using a high-angle annular dark field detector, as well as by differential phase contrast analysis. In-depth structural characterization of the nanowalls by drop-by-drop ex situ FE-SEM analysis provides insight into possible structure formation mechanisms. Further investigation addresses the thermal stability of the particle morphology and the enhancement of the surface-to-volume ratio by heat treatment (examined by N2 physisorption).

Strain parameters at hot rolling of aluminum strips reinforced with steel netting - Stolbchenko, Mykhailo; Makeieva, Hanna; Grydin, Olexandr; Frolov, Yaroslav; Schaper, Mirko (Journal of Sandwich Structures & Materials)
This experiment studied the strain parameters of rolling an aluminum matrix when wire netting is inserted between aluminum layers. During the experiment, two types of stainless steel fabric netting oriented parallel and diagonal to the rolling axis were placed between two aluminum strips and rolled. Multiple rolling processes were performed in which the temperature and pressure on the material were varied to produce bonding of matrix layers. During the study, the following main investigations were made: strain on areas of longitudinal and transverse cross sections of the composite was measured; stretching and ovalization of net wiring and changes in the net cell angles were determined; mechanical properties of composites along the rolling direction were tested. The main contradiction resulting from this experiment was as follows: the contact pressure required for the bonding of aluminum layers produces extreme tensile strain on the inserted net wires, reducing the mechanical properties of the reinforcing net and thus reducing properties of the entire composite. Optimal results in the longitudinal tension tests were achieved by using strips with diagonally oriented net-reinforcement.

Characterization of the fatigue behaviour for SAE 1045 steel without and with load-free sequences based on non-destructive, X-ray diffraction and transmission electron microscopic investigations - Wu, Haoran; Bill, T.; Teng, Z.J.; Pramanik, Sudipta; Hoyer, Kay-Peter; Schaper, Mirko; Starke, Peter (Materials Science and Engineering: A)
Keywords: Mechanical Engineering; Mechanics of Materials; Condensed Matter Physics; General Materials Science

Tribo-mechanical properties and adhesion behavior of DLC coatings sputtered onto 36NiCrMo16 produced by selective laser melting - Tillmann, Wolfgang; Lopes Dias, Nelson Filipe; Stangier, Dominic; Hagen, Leif; Schaper, Mirko; Hengsbach, Florian; Hoyer, Kay-Peter (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry